2010
DOI: 10.1016/j.geomphys.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Lower bounds for the eigenvalues of the Dirac operator on Spinc manifolds

Abstract: In this paper, we extend the Hijazi inequality, involving the Energy-Momentum tensor, for the eigenvalues of the Dirac operator on Spin c manifolds without boundary. The limiting case is then studied and an example is given.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…We can think of the Dirac operator associated to a Spin c structure as the twisted Dirac operator acting on spinors which are twisted by a line bundle. For more details on Spin c structures see [19, Appendix D] and [13,23] for eigenvalue estimates of the Spin c Dirac operator. For this reason the eigenvalue estimate (1.2) can also be interpreted as an eigenvalue estimate of the Dirac operator associated to any Spin c structure and (1.4) as an estimate on the nodal set of a spinor that is in the kernel of the Spin c Dirac operator.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…We can think of the Dirac operator associated to a Spin c structure as the twisted Dirac operator acting on spinors which are twisted by a line bundle. For more details on Spin c structures see [19, Appendix D] and [13,23] for eigenvalue estimates of the Spin c Dirac operator. For this reason the eigenvalue estimate (1.2) can also be interpreted as an eigenvalue estimate of the Dirac operator associated to any Spin c structure and (1.4) as an estimate on the nodal set of a spinor that is in the kernel of the Spin c Dirac operator.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…In this section, we begin with some preliminaries concerning Spin c structures and the Dirac operator. Details can be found in [18], [20], [7], [23] and [24].…”
Section: Preliminariesmentioning
confidence: 99%
“…Next, we will give another proof of the Bär-type inequality (1.3) for the eigenvalues of any Spin c Dirac operator. The following theorem was proved by the second author in [23] using conformal deformation of the spinorial Levi-Civita connection.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Here X · ψ denotes the Clifford multiplication and ∇ the spinorial Levi-Civita connection [9,16]. In [20], it is shown that on a compact Riemannian Spin c manifold any eigenvalue λ of the Dirac operator to which is attached an eigenspinor ψ satisfies the Hijazi type inequality [15] involving the Energy-Momentum tensor and the scalar curvature:…”
Section: Introductionmentioning
confidence: 99%